Aboriginal Women Learning on Country: Lessons for Educators - Goldberg, Lynette R.; Baldock, Dianne; Cox, Terrance; Hoang, Ha; Cross, Merylin; Price, Andrea D. (Frontiers in Public Health, 2022)
Introduction This paper details the journey of eight Aboriginal women from Circular Head, a rural and remote area of North-West Tasmania, as they undertook an innovative 2-year program of tertiary studies in dementia to address a documented community need. The Chief Executive Officer of the Circular Head Aboriginal Corporation (CHAC) had identified difficulties being experienced by older members of the community. These difficulties included changes in behavior, memory, and communication, with profound consequences on social engagement and care needs from both individual and community perspectives. The community wished to know if a combined vocational and university program, completed on Country and in community, could serve as a culturally safe education pathway to empower Aboriginal members of a rural and remote area in providing community health and dementia education and care. Methods The nationally funded program included a year-long face-to-face vocational Certificate III in Individual Support (Aging, Home, and Community) on Country, including within-community experience with adults with dementia. This face-to-face learning was combined with online study in the award-winning Bachelor of Dementia care offered by the University of Tasmania. Students received a PhD level stipend to support them in their studies and were guided by an Elder from their community. Results All students completed their Certificate III. The number of units they completed toward the eight required for their Diploma of Dementia Care varied. Emergent themes from students' reflections were holistic and relational, highlighting achievements and challenges, the importance of on Country individual connections and community support, and the value of their current and future contributions to the community. Data from this mixed methods approach documented the impact of the innovative coupling of authentic, culturally appropriate experiential learning with broad and deep academic knowledge about dementia and evidence-based care. Conclusions This program provided students with a work-related qualification embedded within a university education and increased the capacity and capability of this Aboriginal community to provide care for its members with dementia, a documented concern. The combination of vocational learning on Country with online university study established a pathway to improve students' access to and success in higher education and the professional workforce. This assisted in counteracting the negative influences of racism, stigma, rurality, and socio-economic marginalization on educational opportunity for Aboriginal people. Data showed the need for flexibility with this learning journey, and the strengths and resilience of these women as they learned.